2011
DOI: 10.1021/ie200723w
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Evaluation of CO2 Supply and Utilization in Algal Ponds

Abstract: A mathematical model was constructed to simulate the behaviour of an open algal pond particularly with respect to CO 2 supply and utilisation. The algal pond considered takes wastewater as feed, which provides substrate for aerobic bacteria and also nutrients for the algal-bacterial consortium. CO 2 -containing gas such as flue gas or biogas is considered as additional source of CO 2 to support the growth of algae which at the same time also serves the purpose of CO 2 abatement. A number of simulation studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 29 publications
4
65
0
Order By: Relevance
“…Even when the soil is nearly saturated, the rate is ∼ 1-10 s −1 ( → 1, θ ≈ θ s ). For comparison, studies on waste water treatment used the rate of ≈ 6.9 × 10 −5 s −1 (Buhr and Miller, 1983;Yang, 2011). Thus, mass transfer between gas and liquid in unsaturated soils is assumed to be rapid, and the concentration at each phase is always at equilibrium following Henry's law:…”
Section: Mass Transfer Between Gas and Liquidmentioning
confidence: 99%
See 1 more Smart Citation
“…Even when the soil is nearly saturated, the rate is ∼ 1-10 s −1 ( → 1, θ ≈ θ s ). For comparison, studies on waste water treatment used the rate of ≈ 6.9 × 10 −5 s −1 (Buhr and Miller, 1983;Yang, 2011). Thus, mass transfer between gas and liquid in unsaturated soils is assumed to be rapid, and the concentration at each phase is always at equilibrium following Henry's law:…”
Section: Mass Transfer Between Gas and Liquidmentioning
confidence: 99%
“…Some mathematical models have introduced pH estimation for systems with phototrophs under light-dark cycles, such as algal ponds (Buhr and Miller, 1983;Yang, 2011;Gomez et al, 2014) and phototrophic biofilms (Wolf et al, 2007). The algal pond models invoke solution equilibrium and charge neutrality and employ differential algebraic equations to estimate pH, while the phototrophic biofilm models consider acid-base reactions with rate equations by proposing near-equilibrium kinetics.…”
Section: Mass Transfer Between Gas and Liquidmentioning
confidence: 99%
“…Although this study was the first to optimize CO 2 utilization for biofilm cultivations, the results are in the high range of results with suspension cultivations. Two studies demonstrated CO 2 utilization efficiencies around 70% without significant productivity penalties (Valiorgue et al 2014;Yang 2011). Other studies report CO 2 utilization efficiencies up to 95%, however, the implications for biomass productivity were not quantified (Doucha and Lívanský 2006;Rubio et al 1999).…”
Section: Maximization Of Co 2 Utilization and Biomass Productivity Bymentioning
confidence: 99%
“…For microalgae grown in suspended cultures, processes with minimal CO 2 loss have been developed by employing experimentally validated models (Doucha and Lívanský 2006;Rubio et al 1999;Valiorgue et al 2014;Yang 2011). Their primary conclusion is that CO 2 utilization can be improved by increasing the mass transfer from the gas to the liquid (Doucha and Lívanský 2006;Rubio et al 1999;Valiorgue et al 2014;Yang 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation